Economic benefits of treating medication-overuse headache – results from the multicenter COMOESTAS project. (February 2019) - Jellestad, Pernille Linde; Carlsen, Louise Ninett; Westergaard, Maria Lurenda; Munksgaard, Signe Bruun; Bendtsen, Lars; Lainez, Miguel; Fadic, Ricardo; Katsarava, Zaza; Goicochea, Maria Teresa; Spadafora, Santiago; Jensen, Rigmor Højland; Nappi, Giuseppe; et al.
Background: Medication-overuse headache is a costly disease for individuals and society. Objective: To estimate the impact of medication-overuse headache treatment on direct and indirect headache-related health care costs. Methods: This prospective longitudinal study was part of the COMOESTAS project (COntinuous MOnitoring of Medication Overuse Headache in Europe and Latin America: development and STAndardization of an Alert and decision support System). Patients with medication-overuse headache were included from four European and two Latin American headache centers. Costs of acute medication, costs of health care services, and measurements of productivity were calculated at baseline and at 6-month follow-up Treatment consisted of overused drug withdrawal with optional preventive medication. Results: A total of 475 patients (71%) completed treatment and were followed up for 6 months. Direct health care costs were on average reduced significantly by 52% ( p  < 0.001) for the total study population. Significant reductions were seen in both number of consumed tablets (−71%, p  < 0.001) and number of visits to physicians (−43%, p  < 0.001). Fifty percent of patients reduced their number of consumed tablets ≥ 80%. Headache-related productivity loss, calculated either as absence from work or ≥ 50% reduction of productivity during the workday, were reduced by 21% and 34%, respectively ( p  < 0.001). Conclusion: Standardized treatment of medication-overuse headache in six countries significantly reduced direct health care costs and increased productivity. This emphasizes the importance of increasing awareness of the value of treating medication-overuse headache. Trial registration: The trial was registered at ClinicalTrials.gov (no. NCT02435056)